Ecological Study of Climate Effects on Malaria Incidence in Jayapura Indonesia 2010-2022 - Ora Iring Hutasoit (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Malaria is still a health problem in Indonesia with high geography, rainfall and humidity. Malaria infects people living in endemic areas, especially in tropical and subtropical countries. Malaria can be a public health threat in remote areas. Jayapura is one of the cities in Indonesia with a high incidence of malaria. This event is supported by the geographical position and dominant topography in the form of swamp areas, sago forests, forests, mountains, and environmental influences such as temperature, rainfall, and air humidity. This study aimed to determine the effect of climatic factors consisting of monthly cumulative rainfall, average air temperature monthly average and monthly average relative humidity on the number of monthly malaria cases in Jayapura. Methods: This study uses observation by using ecological-based studies and ecological time-trend design. Results: This study found that rainfall and the incidence of malaria in the city of Jayapura in 2010-2022 had a significant relationship and had a positive relationship at lag 2 in 2010. Air temperature and malaria in the city of Jayapura in 2010-2022 had a significant relationship and had a positive lag 2 in 2010 and 2011. The relative humidity and incidence of malaria in Jayapura in 2010-2022 had a significant relationship and had a negative relationship at a 2-month lag in 2011 and 2015 while in 2013 and 2014 it had a strong and positive relationship. Conclusion: Ecological studies found a significant relationship between climate and malaria incidence in Jayapura.